A facile strategy to realize a single/double photon excitation-dependent photosensitizer for imaging-guided phototherapy against HeLa cancer cells at separate irradiation channels. Issue 4 (12th December 2019) - Kong, Lin; Huang, Ze; Zhang, Shuai-Shuai; Song, Jian; Zhang, Yu-Yang; Bai, Xiang-Yang; Yang, Jia-Xiang; Li, Lin
Abstract : A facile strategy has been proposed to realize two-photon phototherapy against HeLa cancer cells with simultaneous one-photon fluorescence imaging modality at separate irradiation channels. Abstract : A novel difluoroboron fluorophore with an electron donor–acceptor conjugated structure was synthesized with 26.5% fluorescence quantum yield, 18 035 GM two-photon absorbing cross-section, and undetectable two-photon fluorescence, resulting in 25% 1 O2 quantum yield. The unique optical behavior of CNFBBN enabled one-photon fluorescence imaging and two-photon phototherapy against HeLa cancer cells, irradiated at separate wavelengths.